Simultaneous Quantification of Seven Antifungal Agents in Human Serum Using Liquid Chromatography-Tandem Mass Spectrometry - Wenjing Li; Yang Li; Junlong Cai; Yue Wang; Yanan Liu; Hankun Hu; Liang Liu (MDPI AG, 2023)
Systemic antifungal agents are essential for high-risk patients undergoing immunosuppressive therapy or cancer chemotherapy because of the rapid increase in opportunistic fungal infections. Therapeutic drug monitoring is crucial to ensuring the efficacy and safety of antifungal agents owing to their pharmacokinetic variability. In the present study, we developed and validated a quantitative method for the simultaneous detection of seven commonly used antifungal drugs (amphotericin B, isavuconazole, voriconazole, fluconazole, posaconazole, caspofungin, and micafungin) using liquid chromatography-tandem mass spectrometry. Methanol (containing 0.1% formic acid) was used for protein precipitation and only 50 μL of serum was required for the analysis. Chromatographic separation was conducted using a Waters Acquity UPLC C8 column, and one stable isotope-labeled agent and two analogs were used as internal standards. The calibration curves ranged from 0.1 to 50 μg/mL for all agents, and the correlation coefficient (R2) for all calibration curves was above 0.9835. The intra-day precision (1.2-11.2%), inter-day precision (2.4-13.2%), and mean bias values (−10.9 to 13.6%) were within an acceptable range of ±15%. Successful implementation of the developed method in clinical practice would facilitate the effective monitoring of these antifungal agents.